ANALISIS KEBANGKRUTAN PERUSAHAAN DENGAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - B.M.S, Rio Evans; Ermiati, Cut (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2015)
This study examines the analysis of bankruptcy which uses a model Altman Z-Score 1983 once studied the effect of variable ratio of Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Tax to Total Assets (X3), Book Value of Equity to Book Value of Total Debt (X4), and Sales to Total Assets (X5) against bankruptcy for companies that went bankrupt or for companies that are not bankrupt by the number of samples (purposive sampling as a sampling technique ) as many as 15 companies. The purpose of this study is to analyze the financial ratios Altman model to explain the companys financial condition foods and beverages as a first step in anticipation of bankruptcy. The analysis method in this research is to perform calculations using the Altman Z-Score Revised (1983) and multinomial logit analysis. Testing is done with the first models prerequisite analysis, testing normality with the overall result is a variable based test One Sample Kolmogorov-Smirnov test indicated that the model in an abnormal position with evidence of significant data Î± > 0.05. Second, the test results with the results multikolinieritas with VIF < 10 and the tolerance level of > 0.1 indicates that our model is free from the problems of multicollinearity. This is consistent with the assumption multinomial logit analysis that does not require the classical assumption that multinomial logit analysis can proceed. The results of this study are the calculations that have been done, that there are 10 companies in the category of Grey Area and 5 companies in the category is not bankrupt. Seen as a whole has a classification of 95%, while the remaining 5% indicates that bankruptcy is explained by other variables other than those examined in this study In this study the variable ratio of Book Value of Equity to Book Value of Total Debt and Sales to Total Assets have influence significantly to the bankruptcy analysis. So that this research model is Z-Score = Ln (P1/P0) = -149.589 + 117,603BVEBVD + 33,029STA and Z-Score = Ln (P2/P0) = -117.301 + 111,623BVEBVD + 21,657STAÂ Keywords: Bankruptcy, Multinomial Logit Analysis, Financial Ratios Altman Z-Score Model Of Revision.